ANALISIS PENETAPAN NILAI GANTI KERUGIAN PROPERTI KORBAN LUAPAN LUMPUR LAPINDO (JEJAK, 2010)
This research studies the fairness of the agreed compensation property nominal value for the victims of the Sidoarjo mudflow. This research was performed by comparing the agreed nominal amount of compensation with the estimated values based on the property price model. The model was developed based on the market property (lands and houses) prices at the region in normal condition before disaster. The market property price is then adjusted based on the principal of time value of money. Property in this research is limited to losses of lands and houses. Analysis tool which was used for estimating property value in normal condition is multiple linear regression using theOrdinary Least Square. The significance of one-sample tests of hypothesis using testing for a population mean was utilized to examine the fairness of compensation determination by PT. Lapindo Brantas, Inc. compared to the real property price. Results of analyses show that the variables of land area, house area, road width in front of houses and lands, transaction time, house quality affect significantly and positively with the R2 value of 0.904033. Analysis results also confirm that the property compensationet property compensation. Results of the population mean significance test shows that nominal compensation price agreed on December 4 2006 is higher than the calculated real price on normal condition (over assessment). determined by PT.Lapindo Brantas, Inc. is statistically different from the mark